Neuroscience and education: how best to filter out the neurononsense from our classrooms? - Purdy, Noel (Irish Educational Studies, 2008)
This article considers the extent to which neuroscience is being applied to education, both on a classroom level and also on the level of curricular reform in Northern Ireland. The article reviews recent research in the area of neuroscience and education and examines a number of popular ‘neuromyths’. It urges the educational world to take a more informed, cautious and critical approach to neuroscience in education, not least in terms of the Northern Ireland Revised Curriculum, and also makes a plea to the neuro scientific community to police in a more rigorous way the application and misapplication of research findings in schools.